The relationship between market orientation and new product performance in Sabah property industry - Evelyn Jublee (2008)
This research is aimed to examine the impact of market orientation towards new product performance in Sabah property industry. The study also investigate the intervening factors of product advantage, product value and marketing advantage on their roles to strengthen the relationship between market orientation and new product performance. A total of twenty two (22) Sabah property developers were selected as a sampling population for the study. From the twenty two (22) property developers there were eighty eight (88) products selected as the unit of analysis for the research study. The instruments to measure independent and dependent variables were adapted from the studies done by Langerak et al. 2004 and Wei & Morgan 2000, while the intervening variables were adapted from studies done by Zirger & Maidique, 1990, Li, 2000 and Langerak et al. 2004. SPSS version 15.0 was used to analyze the data. The finding of the study showed that the independent variable of market orientation is related directly to the new product performance, while the intervening factors of product advantage, product value and marketing advantage proved to strengthen the relationship of between those variables.